Integration of cadastral and financial-accounting systems. (26th September 2008) - Krol, Dariusz; Trawinski, Bogdan; Zawila, Wojciech
Cadastral systems are mission critical systems designed for the registration of parcels, buildings and apartments as well as their owners and users. The maintenance of real estate cadastre registers is in Poland dispersed. So the attempt to create a unified cadastral system is one of the goals of Polish government. Two main IT projects aimed at the creation of an integrated system are presented and discussed. Moreover approaches to assure interoperability between cadastral system and real estate management system and financial-accounting one at the level of a district or a municipality are shown. Bidirectional communication between both systems synchronising data could be feasible.